The ancient Alexandria reflected the Roman look - Clímaco, Joana Campos (Romanitas - Revista de Estudos Grecolatinos, 2013)
Apart from Rome, no city in the early Roman Empire was more characterized and criticized by outsiders than Alexandria. These images produced in Roman times created representations of the city that the contemporary historiography perpetuates: an enormous, beautiful and turbulent city, second only to Rome. The aim of this article is to discuss how these images associated to Alexandria’s greatness and prosperity illustrate a perception of the city as a mirror to Rome and a threat to its hegemony. My objective is to demonstrate that the selection of themes was not innocent, as was not also the duality within the narratives, that focus on Alexandria’s qualities and achievements on the one hand, and on its problems and tendency to polemics, on the other.